2010
DOI: 10.1039/b926064a
|View full text |Cite
|
Sign up to set email alerts
|

Cs9[(γ-PW10O36)2Ru4O5(OH)(H2O)4], a new all-inorganic, soluble catalyst for the efficient visible-light-driven oxidation of water

Abstract: The tetraruthenium-substituted polyoxometalate Cs(9)[(gamma-PW(10)O(36))(2)Ru(4)O(5)(OH)(H(2)O)(4)] was synthesized and structurally, spectroscopically and electrochemically characterized; it was shown to be a catalyst for visible-light-induced water oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 12 publications
0
110
0
2
Order By: Relevance
“…While Ru4PPOM proved capable of oxidizing water, the rate of photodriven water oxidation was approximately 20% lower than with Ru4SiPOM. 135 In an effort to integrate Ru4SiPOM into a PEC, Ru4SiPOM was attached to a TiO 2 nanocrystalline film via ruthenium(II) tris(4,4 0 -dicarboxcylic-2,2 0 -bipyridine). 136 This assembly was investigated spectroscopically and showed that electron transfer between Ru4SiPOM and the ruthenium dye was on the order of a few microseconds and competitive with back electron transfer from the TiO 2 electrode.…”
Section: Water Oxidation Catalystsmentioning
confidence: 99%
“…While Ru4PPOM proved capable of oxidizing water, the rate of photodriven water oxidation was approximately 20% lower than with Ru4SiPOM. 135 In an effort to integrate Ru4SiPOM into a PEC, Ru4SiPOM was attached to a TiO 2 nanocrystalline film via ruthenium(II) tris(4,4 0 -dicarboxcylic-2,2 0 -bipyridine). 136 This assembly was investigated spectroscopically and showed that electron transfer between Ru4SiPOM and the ruthenium dye was on the order of a few microseconds and competitive with back electron transfer from the TiO 2 electrode.…”
Section: Water Oxidation Catalystsmentioning
confidence: 99%
“…There are some reports of photocatalytic water oxidation in homogeneous systems such as molecular ruthenium complexes [125][126][127][128][129][130][131][132][133][134][135], as well as earth abundant metal complexes [136][137][138] in the presence of sacrificial electron acceptors. In this case, a recently published mononuclear ruthenium complex shows TOF values up to 0.32 s −1 [139].…”
Section: Alternatives To Sacrificial Aminesmentioning
confidence: 99%
“…In order to see if catalytic performance could be enhanced, the same authors also synthesized and characterized an isostructural phosphorus-centered tetraruthenium- [55]. On this occasion, photocatalysis was evaluated under visible light illumination (420-520 nm) at pH 5.8 in a Na 2 SiF 6 buffer with an initial turnover frequency reaching 0.13 s 1 .…”
Section: Light-assisted Pom Pathways For Water Oxidationmentioning
confidence: 99%